Prevalence of asthma in young cross-country skiers in central Scandinavia: differences between Norway and Sweden - Sue-Chu, M.; Larsson, L.; Bjermer, L. (Respiratory Medicine, 1996)
An increased prevalence of asthma in cross-country skiers has been reported previously. This study was conducted in order to evaluate the prevalence of asthma among young, elite cross-country skiers in Trondelag, Norway and Jamtland, Sweden. These two regions in central Scandinavia have different climates during the winter season, with a coastal type in Trondelag while Jamtland is characterized by a colder, drier, inland type of climate. The study population consisted of 171 skiers (118 from Norway, 53 from Sweden). The investigation included an asthma questionnaire, spirometry and methacholine provocation testing. The prevalence of self-reported asthma-related symptoms was 46% in Norway and 51% in Sweden. The prevalence of bronchial hyper-responsiveness (BHR) was significantly different between the two regions. In Norway, 14% of the skiers were hyper-responsive to methacholine compared to 43% in Sweden (P < 0.001). Moreover, the estimated prevalence of clinically diagnosed asthma was 12% in Norway and 42% in Sweden (P < 0.001). The self-reported frequency of respiratory allergy was higher in Sweden (32%) than in Norway (11%). However, on an individual basis, self-reported allergy did not predict occurrence of asthma or BHR. In conclusion, there is a high prevalence of BHR and asthma among young, elite cross-country skiers in central Scandinavia, especially in Sweden. Cross-country skiing may be a risk factor for the development of asthma. Longitudinal studies of cross-country skiers, and studies to acquire further knowledge of the mechanisms involved in the development of asthma are indicated.